INTEGRATING NATIONAL HERITAGE AND TRADITIONAL ART IN VISUAL ARTS LESSONS - Nasulloyeva Sarvinoz Komiljon qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines methods for integrating national heritage and traditional art into visual arts lessons. The study focuses on enhancing students’ understanding of national values, developing artistic literacy, and fostering creative thinking. It also discusses effective ways to combine traditional art forms with modern pedagogical approaches in classroom practice. The article provides practical recommendations for teachers and aims to improve the effectiveness and engagement of visual arts education.